The Implementation of High School Remedial Program on Regulation System Material in Palu City Based on School Status and Teachers’ Education Background - P, Fildayana; Djukri, P (FMIPA UNNES, 2019)
This research aims to describe the implementation of a high school remedial program on regulation system materials in Palu City based on school status and teacher’s educational background. This research is descriptive research with a mono variable using the survey method. The subject of this research was biology teacher class XI and class XI students who followed the improvement program on system registration material. The variable of this research is qualitative descriptive research. The subject of this research was biology teacher class XI and class XI students who followed the improvement program on system registration material. Data collection techniques using observation, interview, and documentation techniques. Data analysis techniques add data reduction, data presentation, and verification. The validity of lottery data by technical triangulation and source triangulation. Data collection uses Human Instruments, interview guidelines for teachers, and interview guidelines for the student. The data were analyzed using the component analysis technique based on Miles and Huberman. The research result indicated that the implementation of the remedial program on regulation system materials at a public high school in Palu city is better than that of private high school. However, the implementation by teachers whose education background is educational is better than that of those whose educational background is non-educational.